Anisotropic plasma-chemical etching by an electron-beam-generated plasma - Rocca, Jorge J., author; Verhey, T. R., author; Boyer, P. K., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1988)
Anisotropic etching of SiO2 has been achieved with a plasma generated by a broad-area low-energy (150-300 eV) electron beam in a He + CF4 atmosphere. Etch rates of up to 330 Å/min for SiO2 and 220 Å/min for Si were obtained. Etching occurred with good uniformity over the entire area exposed to the electron-beam-generated plasma. The fluxes of energetic charged particles to the sample surface are discussed in relation to their possible contribution to the etching process.